Fast photo-driven electron spin coherence transfer: the effect of electron-nuclear hyperfine coupling on coherence dephasing1. Issue 30 (14th August 2015) - Krzyaniak, Matthew D.; Kobr, Lukáš; Rugg, Brandon K.; Phelan, Brian T.; Margulies, Eric A.; Nelson, Jordan N.; Young, Ryan M.; Wasielewski, Michael R.
<x xml:space="preserve">Abstract</x> A covalently-linked electron donor–acceptor–acceptor molecule was utilized to study the effect of electron-nuclear hyperfine coupling on the dephasing of the zero quantum coherence in spin correlated radical pairs.